Extending Our Scientific Reach in Arboreal Ecosystems for Research and Management - Cannon, Charles H.; Borchetta, Colby; Anderson, David L.; Arellano, Gabriel; Barker, Martin; Charron, Guillaume; LaMontagne, Jalene M.; Richards, Jeannine H.; Abercrombie, Ethan; Banin, Lindsay F.; Tagle Casapia, Ximena; Chen, Xi; et al. (Frontiers in Forests and Global Change, 2021)
The arboreal ecosystem is vitally important to global and local biogeochemical processes, the maintenance of biodiversity in natural systems, and human health in urban environments. The ability to collect samples, observations, and data to conduct meaningful scientific research is similarly vital. The primary methods and modes of access remain limited and difficult. In an online survey, canopy researchers (n=219) reported a range of challenges in obtaining adequate samples, including ~10% who found it impossible to procure what they needed. Currently, these samples are collected using a combination of four primary methods: 1) sampling from the ground; 2) tree climbing; 3) constructing fixed infrastructure; and 4) using mobile aerial platforms, primarily rotorcraft drones. An important distinction between instantaneous and continuous sampling was identified, allowing more targeted engineering and development strategies. The combination of methods for sampling the arboreal ecosystem provides a range of possibilities and opportunities, particularly in the context of the rapid development of robotics and other engineering advances. In this study, we aim to identify the strategies that would provide the benefits to a broad range of scientists, arborists, and professional climbers and facilitate basic discovery and applied management. Priorities for advancing these efforts are 1) to expand participation, both geographically and professionally; 2) to define 2-3 common needs across the community; 3) to form and motivate focal teams of biologists, tree professionals, and engineers in the development of solutions to these needs; and 4) to establish multidisciplinary communication platforms to share information about innovations and opportunities for studying arboreal ecosystems.